Laser‐generated ns plasma pulses characterized using SiC Schottky diode. Issue 7 (11th March 2020) - Torrisi, Lorenzo; Torrisi, Alfio; Cutroneo, Mariapompea
Abstract: The nonequilibrium plasma generated by nanosecond laser pulse is characterized using a SiC detector connected in time‐of‐flight configuration to measure the radiations emitted from the plasma. Different metallic targets were irradiated by the pulsed laser at an intensity of 10 10  W/cm 2 and 200 mJ pulse energy. The SiC allows detecting ultraviolet radiations and soft X‐rays, electrons, and ions. The obtained plasma has a temperature of the order of tens to hundreds eV depending on the atomic number of the irradiated target and ion accelerations of the order of 100 eV per charge state.